Respuesta :

Answer:

Simplifying

3n + 7 + -2 = 0

Reorder the terms:

7 + -2 + 3n = 0

Combine like terms: 7 + -2 = 5

5 + 3n = 0

Solving

5 + 3n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-5' to each side of the equation.

5 + -5 + 3n = 0 + -5

Combine like terms: 5 + -5 = 0

0 + 3n = 0 + -5

3n = 0 + -5

Combine like terms: 0 + -5 = -5

3n = -5

Divide each side by '3'.

n = -1.666666667

Simplifying

n = -1.666666667

Step-by-step explanation:

ACCESS MORE